Poppy and Rye - Avi, 1937-; Floca, Brian (HarperTrophy, 2007)
When their home next to a brook is destroyed by beavers, a large family of golden mice is aided by Poppy the deer mouse and her grumpy porcupine friend, who in the process forges a relationship with the son he had abandoned.
620
Accelerated Reader AR
Keywords: Mice -- Juvenile fiction; Porcupines -- Juvenile fiction; Animals -- Juvenile fiction; Fathers and sons -- Juvenile fiction; Mice -- Fiction; Porcupines -- Fiction; Animals -- Fiction; Fathers and sons -- Fiction